Perilaku Pacaran pada Peserta Didik SMP X (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Adolescence is the transition from childhood to early adulthood. Childhood as we know Together, they make friends with the same and the opposite sex without awkwardness and shame. Even though they believe that they are no longer children, the people around them still believe that they are still children. This study uses a qualitative methodology. Junior high school children were used as subjects. Data collection techniques from subjects using interviews. In some of the subjects we interviewed, their behavior when they were dating especially when the two of them were just chatting, studying together, worshiping together, spoiled like little children. Dating activities among junior high school students is a normal and natural phase experienced by teenagers, especially those who are going through puberty. Dating itself is two people who love each other, are willing to do anything to make their partner happy and have a future goal of being a companion for life forever, which is called marriage. Keywords: Teenagers, Dating, Behavior, love language